Positron annihilation spectroscopic investigation of high energy ball – milling engendered defects in CaCu3Ti4O12. Issue 13 (September 2018) - Raval, P.Y.; Pansara, P.R.; Vasoya, N.H.; Modi, K.B.; Nambissan, P.M.G.
Abstract: Polycrystalline sample of calcium – copper – titanate (CaCu3 Ti4 O12 ) was synthesized by two – steps solid state reaction route and then high energy ball-milled for several hours. Samples collected at different hours of milling were characterized and studied. X-ray diffraction patterns indicated monophase formation in the initial stage of grinding and a few other phases were found being formed with further milling. The elemental analysis indicated the possible presence of defects possibly due to non-stoichiometry, which was subsequently confirmed through positron annihilation studies. The positron trapping defects in the samples were found evolving from monovacancies to larger vacancy clusters and microvoids during increased hours of milling. The concomitant process of reduction of the sizes of the crystallites to nanometre dimensions resulted in the diffusion of thermalized positrons to the nanocrystallite surfaces and subsequent annihilation. The results indicated defects as a strong entity of influence on the structure and properties of CaCu3 Ti4 O12 and deserving serious consideration when the high dielectric material is sought for use in practical applications.